Changes in external ischial tuberosity width at varying trunk–thigh angles between sexes using two measurement methods - Yi-Lang Chen (Nature Portfolio, 2021)
Abstract This study examined the influence of two methods and various trunk–thigh (TT) angles on external ischial tuberosity width (EITW) for 45 men and 45 women. In the experiment, the impress and seat pressure methods were applied at TT angles of 60°, 75°, 90°, and 105°. When the impress method was used, EITW remained highly consistent across the four measured TT angles with differences of 2.8 and 2.1 mm for men and women, respectively. Conversely, in the seated pressure method, EITW increased with TT angle such that differences in EITW across a full TT angle range were 11.5 and 11.7 mm for men and women, respectively. Irrespective of method, differences in EITW between genders measured approximately 12.6–13.7 mm across all TT angles. Correlation analyses revealed that hip circumference was positively related to EITW in all cases, whereas the relationship of hip width and depth with EITW varied by method and gender. Because of inherent differences in EITW between genders, these findings suggest that gender variability should be considered in seat cushion design.